Meeting Report: 7(th) World Congress on Itch - Azimi, Ehsan (2014)
The 7th World Congress on Itch was held in Boston in September 2013. This is the biennial meeting of the International Forum for the Study of Itch (IFSI), www.itchforum.net, There were 240 attendees from 17 countries. They spanned clinical practice, academics and patient advocacy while the opportunity for translation was demonstrated as 80 attendees were from industry. A large academic neuroscience contingent was present. There were plenary sessions, basic and clinical tracts, and sixty posters during the 2½ day meeting. The meeting program and 160 abstracts are available at www.itchboston.org and the open access journal, Acta Dermato-Venereologica, www.medicaljournals.se/acta/. This report highlights selected aspects of the congress and the latest advances in the field.